Probing Protein Surface with a Solvent Mimetic Carbene Coupled to Detection by Mass Spectrometry - Gomez, Gabriela Elena (2011)
Much knowledge into protein folding, ligand binding, and complex formation can be derived from the examination of the nature and size of the accessible surface area (SASA) of the polypeptide chain, a key parameter in protein science not directly measurable in an experimental fashion. To this end, an ideal chemical approach should aim at exerting solvent mimicry and achieving minimal selectivity to probe the protein surface regardless of its chemical nature. The choice of the photoreagent diazirine to fulfill these goals arises from its size comparable to water and from being a convenient source of the extremely reactive methylene carbene (:CH2). The ensuing methylation depends primarily on the solvent accessibility of the polypeptide chain, turning it into a valuable signal to address experimentally the measurement of SASA in proteins. The superb sensitivity and high resolution of modern mass spectrometry techniques allows us to derive a quantitative signal proportional to the extent of modification (EM) of the sample. Thus, diazirine labeling coupled to electrospray mass spectrometry (ESI-MS) detection can shed light on conformational features of the native as well as non-native states, not easily addressable by other methods. Enzymatic fragmentation of the polypeptide chain at the level of small peptides allows us to locate the covalent tag along the amino acid sequence, therefore enabling the construction of a map of solvent accessibility. Moreover, by subsequent MS/MS analysis of peptides, we demonstrate here the feasibility of attaining amino acid resolution in defining the target sites.